A Case of Infective Endocarditis Associated With Patent Ductus Arteriosus in Which PET/CT Was Useful for Diagnosis. (11th September 2022) - Miyagami, Taiju; Kushiro, Seiko; Arikawa, Mari; Murakami, Koji; Naito, Toshio
Abstract: A 33-year-old woman presented to our hospital with a 4-month history of fever of unknown origin. Physical examination revealed a vascular murmur in the left subclavian region. Blood culture revealed bacteria and PET/CT revealed tracer accumulation in the patent ductus arteriosus area, leading to the diagnosis of infective endocarditis in this area. This case report may aid in diagnosing this disease in the future, as infective endocarditis in a patent ductus arteriosus is rare and difficult to diagnose.